Odd-even alternation in tautomeric porous organic cages with eceptional chemical stability - Bera, S.; Basu, A.; Tothadi, S.; Garai, B.; Banerjee, S.; Vanka, K.; Banerjee, R. (Angewandte Chemie-International Edition, 2017)
Amine-linked (C-NH) porous organic cages (POCs) are preferred over the imine-linked (C= N) POCs owing to their enhanced chemical stability. In general, aminelinked cages, obtained by the reduction of corresponding imines, are not shape-persistent in the crystalline form. Moreover, they require multistep synthesis. Herein, a one-pot synthesis of four new amine-linked organic cages by the reaction of 1,3,5-triformylphloroglucinol (Tp) with different analogues of alkanediamine is reported. The POCs resulting from the odd diamine (having an odd number of -CH2 groups) is conformationally eclipsed, while the POCs constructed from even diamines adopt a gauche conformation. This odd-even alternation in the conformation of POCs has been supported by computational calculations. The synthetic strategy hinges on the concept of Schiff base condensation reaction followed by keto-enol tautomerization. This mechanism is the key for the exceptional chemical stability of cages and facilitates their resistance towards acids and bases.